New species and distribution notes of Cerambycidae (Coleoptera) for the state of Acre and the Amazon basin, Brazil - Monné, Marcela L.; Monné, Miguel A. (Zootaxa, 2018)
A new species, Unachlorus rafaeli sp. nov., is described from Brazil, state of Acre. Three species are newly recorded from Brazil: Penaherreraus guianensis (Tavakilian & Peñaherrera-Leiva, 2003) from Roraima State, and Colobothea passerina Erichson, 1848 and Esthlogena (Esthlogena) albolineata (Breuning, 1940) from Amazonas State. Thirty-two species are new state records, 19 from Roraima, 10 from Amazonas and three from Acre.